Female Mice Exposed to Postnatal Neglect Display Angiotensin II–Dependent Obesity‐Induced Hypertension - Dalmasso, Carolina (J Am Heart Assoc, 2019)
BACKGROUND: We have previously reported that female mice exposed to maternal separation and early weaning (MSEW), a model of early life stress, show exacerbated diet‐induced obesity associated with hypertension. The goal of this study was to test whether MSEW promotes angiotensin II–dependent hypertension via activation of the renin‐angiotensin system in adipose tissue. METHODS AND RESULTS: MSEW was achieved by daily separations from the dam and weaning at postnatal day 17, while normally reared controls were weaned at postnatal day 21. Female controls and MSEW weanlings were placed on a low‐fat diet (LF, 10% kcal from fat) or high‐fat diet (HF, 60% kcal from fat) for 20 weeks. MSEW did not change mean arterial pressure in LF–fed mice but increased it in HF–fed mice compared with controls (P<0.05). In MSEW mice fed a HF, angiotensin II concentration in plasma and adipose tissue was elevated compared with controls (P<0.05). In addition, angiotensinogen concentration was increased solely in adipose tissue from MSEW mice (P<0.05), while angiotensin‐converting enzyme protein expression and activity were similar between groups. Chronic enalapril treatment (2.5 mg/kg per day, drinking water, 7 days) reduced mean arterial pressure in both groups of mice fed a HF (P<0.05) and abolished the differences due to MSEW. Acute angiotensin II–induced increases in mean arterial pressure (10 μg/kg SC) were attenuated in untreated MSEW HF–fed mice compared to controls (P<0.05); however, this response was similar between groups in enalapril‐treated mice. CONCLUSIONS: The upregulation of angiotensinogen and angiotensin II in adipose tissue could be an important mechanism by which female MSEW mice fed a HF develop hypertension.